Palmprint Recognition For Personal Identification System - Tee , Connie (2004)
Palmprint is well-known for several advantages such as stable line features, low-resolution imaging, low-cost capturing device, and user-friendly. In this thesis, an automated scanner-based palmprint recognition system is proposed. The system automatically captures and aligns the palmprint images for processing. The proposed palmprint recognition system consists of two important stages namely the enrollemnt and recognition components. In the enrollment stage, the palmprint images acquired are first aligned by the pre-processing step. After that, important palmprint features are extracted to generate matching templates to be stored in the database. In the verification stage, a new palam print image is also processed bt the pre-processing and feature extraction module, and then matched with the stored reference template to determine whether it belongs to a genuine template.